Pseudoaneurysm of Internal Carotid Artery Following Mandibular Reconstruction Treated by Covered Stent - Mejdoubi, M. (Centauro S.r.l., 2006)
We describe the case of a 68-year-old woman who had a mandibular titanium plate reconstruction following surgery for a parotid carcinoma. Fifteen months later she presented bleeding episodes related to a pseudoaneurysm of the internal carotid artery located just above the bulb. This was probably related to the weakening of the arterial wall following friction with the mandibular plate and radiotherapy. We successfully obliterated this pseudoaneurysm using a covered stent. This rare diagnosis should be evoked in case of bleeding following a mandibular reconstruction. Stenting is an effective treatment strategy obviating the need for open surgery.